KEMAMPUAN BERPIKIR KREATIF SISWA DALAM PENYELESAIAN SOAL OPEN-ENDED MATERI STATISTIKA PADA KELAS IX SMP - Salim, Abdul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract Students' creative thinking ability is one of their abilities that must be developed in Mathematics learning process. In fact, many teachers at school didn't give their attention to this ability. By knowing students' ability and students' creative thinking process, teacher will be able to know students' potential and talent. This research aimed to describe students' ability to think creatively in solving open ended question in grade IX SMP. This research was a descriptive research. Subject of this research was one of class IX which consists of 21 students. Data was collected by some instruments to assess students' ability to think creatively, they are test or open ended questions. The result of this research showed that students' ability in thinking creatively was categorized as good, with the percentage of students' mean score was 60.42%. The percentage of fluency reached 76.19% which categorized as good, the percentage of flexibility reached 80.95% which categorized as very good, the percentage of originality reached 63.09% which categorized as enough, and the percentage of ellaboration reached 21.43% which categorized as less. Flexibility aspect was the most dominant ability to appear, while elaboration aspect was the least dominant ability to appear. Keywords: creative thinking, open-ended problem, problem solving